Supporting locomotive functions of a six-legged walking robot - Walas, Krzysztof; Belter, Dominik (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents a method for building a foothold selection module as well as methods for the stability check for a multi-legged walking robot. The foothold selection decision maker is shaped automatically, without expert knowledge. The robot learns how to select appropriate footholds by walking on rough terrain or by testing ground primitives. The gathered knowledge is then used to find a relation between slippages and the obtained local shape of the terrain, which is further employed to assess potential footholds. A new approach to function approximation is proposed. It uses the leastsquares fitting method, the Kolmogorov theorem and population-based optimization algorithms
Keywords: robotics; walking robots; foothold placement; static stability